Fantasia do movimento : a interação entre o corpo real e o virtual dos desenhos animados - Silva, Rayssa Oliveira e (Universidade do Estado do Amazonas, 2019)
In this text, we study the choreographic similarities of the cartoon Fantasia (1940) with the spectacles that served as reference for the creative process of the drawing like Sacre du Printemps, Suite Nutcracker and Dance of the Hours. The analysis also runs through scenographic and narrative aspects in order to corroborate with the choreographic analysis. For this, a historical approach is first made to the relationship between dance and technology, which is the link between these two worlds, the real and the imaginary. In order to investigate in a profound way the relation of movement between these two universes, we use the considerations proposed by Rudolf Laban (1879-1958) being applied to the bodies of the cartoons and also the application of the labanotation to have another perception of the choreography. The results indicate that there are similarities to elements of the scenic show and the reflections allow us to verify the possibilities of the understanding of the movement and the space-time in the dance, making possible new interpretations and theoretical associations. In addition, similar choreographic aspects also appear with respect to movement and intentions of communication . Keywords: Cartoon, Dance, Laban, Choreography, Analyze